Diversity of Bacterial Communities Associated with Solitary Bee Osmia excavata Alfken (Hymenoptera: Megachilidae) - Liu, Wenping; Li, Yue; Lu, Huanhuan; Hao, Youjin; Zhang, Ke; Dang, Xiaoqun; Fan, Xiaodong; Zhang, Huan; Zhou, Zeyang; Zhu, Chaodong; Luo, Arong; Huang, Dunyuan (Applied sciences, 2023)
Insect-associated microorganisms play important roles in the health and development of insects. This study aimed to investigate the similarities and differences in bacterial community structure and composition between the larval gut of Osmia excavata, nest soil, and brood provision from the nest tube. We sequenced larvae gut and their environments’ microorganisms of O. excavata from four locations based on full-length 16S rRNA gene amplicons. The results showed 156, 280, and 366 bacterial OTUs from gut, brood provision, and nest soil, respectively, and three groups shared 131 bacterial OTUs. In the gut, the top two dominant bacteria were Sodalis praecaptivus (68.99%), Lactobacillus micheneri (17.95%). In the brood provision, the top two dominant bacteria were S. praecaptivus (26.66%), Acinetobacter nectaris (13.05%), and in the nest soil, the two most abundant bacteria were Gaiella occulta (4.33%), Vicinamibacter silvestris (3.88%). There were significant differences in diversity between the brood provision groups and the nest soil groups, respectively. Three of the four locations did not differ for gut microbial diversity. Bacteria similar to other solitary bees also existed in the gut of the larvae. Results indicated when the habitat environments were similar, the bacterial community diversity of the gut of O. excavata was similar, despite significant differences among brood provisions and soils, respectively.